Wound Care Management Using Transparent Film Dressing For Reduced Eyelid Edema Skin Elderly - Warja, Rubiyanto (Journal of Ageing And Family, 2023)
Introduction: In western and develop our countries chronological 65 years is considered as beginning of aging, Elderly need accompaniment person such as caregiver and especially material in house to prevent risk of fall and causes of infection or inflammation delay healing in elderly lose skin integrity, decrease elastin and collagen difficult to healing wounds and hard to heal category. Method: case study, reporting grandma (76 years old) slipped in bathroom and has a bruise or edema left eyelid she cannot open the eye, wound care management and skin recovery using transparent film dressing as topical therapeutic therapy for released inflammatory phases in wound healing process. Result: Using transparent film dressing twice application (six days) and changing the dressing every 3 days effective for released edema left eyelid. Conclusion: The skin loses elasticity, it becomes fragile of skin, dry skin, decrease of skin integrity like tears, bruises and the other, older adults are at risk getting the wounds. Decreased skin elasticity and collagen are causes of difficult healing of the wound and in many cases delay inflammation or prolong infection, using transparent film dressing for topical therapeutic therapy effective for reduced edema skin elderly in six days. Keywords : Transparent film dressing, Reduced edema, Skin elderly